Resistance to fluoroquinolones in Escherichia coli isolated from poultry. - Bazile-Pham-Khac, S (1996)
Quinolone-resistant Escherichia coli strains were isolated from poultry clinical samples in Saudi Arabia. The poultry flocks had been treated with oxolinic acid or flumequine prophylaxis. The measure of the uptake of fluoroquinolones showed that none of the strains had a reduced accumulation of quinolones. The result of complementation with the wild-type E. coli gyrA gene, which restored fluoroquinolone susceptibility, and the isolation of DNA gyrase from six isolates indicated that the resistant strains had an altered DNA gyrase. The minimum effective dose of ciprofloxacin for inhibition of supercoiling catalyzed by the isolated gyrases varied from 0.085 microgram/ml for a susceptible isolate (MIC < 4 micrograms/ml) up to 96 micrograms/ml for the more resistant one (strain 215, MIC > 64 micrograms/ml). For the same two isolates, the minimum effective doses of sparfloxacin varied from 0.17 up to 380 micrograms/ml. The in vitro selection of spontaneous single-step fluoroquinolone-resistant mutants using ciprofloxacin suggested that the more resistant mutants are likely the result of several mutations. These results also show that, as in human medicine, cross-resistance between older quinolones and fluoroquinolones can exist in veterinary isolates and reiterate the need for the prudent use of these drugs.